Quality of Primary Care Provided to Medicare Beneficiaries by Nurse Practitioners and Physicians. Issue 6 (June 2018) - Buerhaus, Peter; Perloff, Jennifer; Clarke, Sean; O'Reilly-Jacob, Monica; Zolotusky, Galina; DesRoches, Catherine M.
Abstract : Objective: To examine differences in the quality of care provided by primary care nurse practitioners (PCNPs), primary care physicians (PCMDs), or both clinicians. Data Sources: Medicare part A and part B claims during 2012–2013. Study Design: Retrospective cohort design using standard risk-adjustment methodologies and propensity score weighting assessing 16 claims-based quality measures grouped into 4 domains of primary care: chronic disease management, preventable hospitalizations, adverse outcomes, and cancer screening. Extraction Methods: Continuously enrolled aged, disabled, and dual eligible beneficiaries who received at least 25% of their primary care services from a random sample of PCMDs, PCNPs, or both clinicians. Principal Findings: Beneficiaries attributed to PCNPs had lower hospital admissions, readmissions, inappropriate emergency department use, and low-value imaging for low back pain. Beneficiaries attributed to PCMDs were more likely than those attributed to PCNPs to receive chronic disease management and cancer screenings. Quality of care for beneficiaries jointly attributed to both clinicians generally scored in the middle of the PCNP and PCMD attributed beneficiaries with the exception of cancer screening. Conclusions: The quality of primary care varies by clinician type, with different strengths for PCNPs and PCMDs. These comparative advantages should be considered when determining how to organize primary care to Medicare beneficiaries. Abstract : Supplemental Digital Content is available in the text.